Case Report: Tumor-to-tumor metastasis with prostate cancer metastatic to lung cancer: the first reported case - Liu, Shiyue; Li, Hong; Dong, Youhong; Zhang, Dongdong (Frontiers in Oncology, 2023)
Tumor-to-tumor metastasis (TTM) occurs rarely in tumor progression, but this event has significant clinical implications. Although the impact of TTM on patient prognosis and survival has been increasingly recognized, understanding of TTM biology and treatment is limited.Prostate cancer is among the most common malignancies threatening male health. Prostate cancer can potentially metastasize to primary lung Cancer; however, this is an exceedingly rare event. We here report for the first time a case of TTM from a prostate cancer to a coexisting primary lung cancer.